The effects of motivational and metacognitive variables on immigrant and non-immigrant students' reading achievement. (2022) - Kaya, Sibel; Eryilmaz, Nurullah; Yuksel, Dogan
Highlights: Motivational and metacognitive variables affected non-immigrant students' reading achievement in all countries. However, motivational and metacognitive variables were not as effective in immigrants' achievement. Perception of reading competence and summarising had positive impact on immigrants' reading achievement in all countries. Explained variances in reading achievement by study variables were considerably higher for non-immigrants than immigrants. Abstract: The purpose of this study was to examine the effects of motivational and metacognitive variables regarding reading on PISA reading achievement for immigrants and non-immigrants in four Anglophone countries. Single-level multiple regression analyses were conducted for immigrants and non-immigrants separately. Motivational and metacognitive variables consistently affected non-immigrant students' reading achievement in each country; however, they were not as effective in immigrants' achievement. Among the motivational variables, perception of reading competence, and among the metacognitive variables, summarising had significant positive effects on immigrants' reading achievement in all countries. Explained variances in reading achievement by the study variables were considerably higher for non-immigrants than immigrants. The outcomes and the implications were discussed.